1969
DOI: 10.1071/bi9691527
|View full text |Cite
|
Sign up to set email alerts
|

Freezing Ram Spermatozoa by the Pellet Method. I. the Effect of Diluent Composition on Survival of Spermatozoa

Abstract: SummaryFive experiments were conducted to examine the effects of different sugars and varying levels of sugar, sodium citrate, and egg yolk in the diluent on the survival of ram spermatozoa following freezing by the pellet method.Highly significant quadratic regressions· relating diluent freezing point depression to the mean percentage of motile spermatozoa assessed during postthawing incubation were demonstrated. Relatively hypertonic diluents gave best results.The optimal diluent freezing point depression, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1969
1969
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Levels ofthis order are considerably lower than those used by Blackshaw (1955aBlackshaw ( , 1955b, Jones and Martin (1965), Salamon and Lightfoot (1969) and Salamon (1970) who all employed diluents which contained sodium citrate. However, First et al (1961) noted a tendency toward decreased survival of ram spermatozoa frozen in diluents based on milk as the level of egg yolk was increased from 3 to 24% (vjv).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Levels ofthis order are considerably lower than those used by Blackshaw (1955aBlackshaw ( , 1955b, Jones and Martin (1965), Salamon and Lightfoot (1969) and Salamon (1970) who all employed diluents which contained sodium citrate. However, First et al (1961) noted a tendency toward decreased survival of ram spermatozoa frozen in diluents based on milk as the level of egg yolk was increased from 3 to 24% (vjv).…”
Section: Discussionmentioning
confidence: 91%
“…Choice of cooling rate, first to the point of freezing and then to the storage temperature of -79°C or lower, has been substantially an empirical process with some workers reporting success with slow rates of cooling where relatively high levels of glycerol have been used (Hill, Godley, and Hurst 1959;Jones and Martin 1965) and others, using lower glycerol levels in diluents having a high content of di-or trisaccharide, have reported success using a "pelleting" technique of freezing which involves freezing at rates of the order of 100°C/min (Salamon 1968(Salamon , 1970Salamon and Lightfoot 1969;Salamon 1969a, 1969b). Mazur (1968Mazur ( , 1970 has published data on the effects of cooling rate and survival of various cells (yeasts, human erythrocytes, mouse marrow stem cells, and hamster lung cells from tissue culture) and has shown in these experiments that cooling rate, nature and level of freeze protective agent (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Ritar and Salmon (1982) reported that tris may act as a buffer against changes in pH and tonicity and fructoseisan energy source. Some investigation found that adding of 20% egg -yolk and 7% glyceol to the diluent was claimed to improve the viability and progressive motility of spermatozoa during storage ( Salamon and Lightfoot, 1969). Storage time had a significant effect on progressive motility, viability and pH up to 3 days post collection.…”
Section: Discussionmentioning
confidence: 99%
“…Pursel et al (2009) reported that the results of five extenders used consisted of Tris (0.164 M) and citric acid (0.055 M) in combination with glucose, fructose, lactose, sucrose or raffinose (0.138 M) indicated that the sugar composition of the extender may effect the development of cold shock resistance during incubation. The sugar composition of semen extenders has previously been shown to be a significant factor during freezing of bull and ram spermatozoa (Salamon and Lightfoot, 1969).…”
Section: Effect Of Maltose Concentration In Dilution On Epididymal Spmentioning
confidence: 99%